Statistical Data Analysis Skills Needs Among Creative Arts Students - Mazdan, Ali Amaran; Puteri Ariana, A.Mohd Puat; Mohd Sharizam, Hamzah; Badrolhisham, Mohamad Tahir (Secholian Publication (Kuala Lumpur, Malaysia), 2022)
Knowledge of data analysis skills is an important knowledge for every student, especially for those who conduct research scientifically. However, is there a need for systematic statistical data analysis skills in the scope of their study among creative arts students? Therefore, this study examines the need for quantitative data analysis skills among creative arts students in the perspective of Alumni, Academician and Industry. This study interviewed 12 alumni, 13 academicians and 10 representatives from the Creative Arts Industry to analyse their perspective. Qualitative analysis method is used to analyze the results of interviews with former students, academicians and the industry. As result, all sample of informants interviewed agreed that Creative Arts Students need data analysis skill using quantitative method.